Penerapan Model Pembelajaran Koperatif Tipe Stad Serta Pengaruhnya Terhadap Kebiasaan Belajar Dan Hasil Belajar Siswa Dalam Mata Pelajaran Bahasa Inggris: (Studi Eksperimen Pada SMP Negeri 1 Kota Pematangsiantar) - Irmasari Irmasari (Pusdikra Publishing, 2022)
Student Teams Achievement Divisions (STAD) is the simplest cooperative learning model and a good model for a novice teacher to use a cooperative approach. The STAD learning model is unique because it involves competition between groups for group awards. Study habits are actions that are routinely done in carrying out learning activities. Learning activities include when receiving lessons in class when repeating lesson material, and dealing with tasks related to learning and activities carried out in order to avoid those that interfere with learning concentration. This experimental research was conducted at SMP Negeri 1 Pematangsiantar with the following results: 1) There are differences in student learning outcomes taught with the STAD-type cooperative learning model and the expository learning model. The mean of English learning outcomes taught with the STAD-type cooperative learning model, amounted to 76.21 and the mean of English learning outcomes with the expository learning model amounted to 73.89, 2) There is a difference in student learning outcomes between those with high learning habits and those with low learning habits. The mean learning outcome of students with high learning habits is 78.96 and the mean learning outcome of students with low learning habits is 71.14, and 3) There is no interaction between learning models and learning habits.